Quintais produtivos na agricultura familiar: caracterização e participação nas compras governamentais no município de Apodi/RN - Sousa, Elaine Patricia de Oliveira (Universidade Federal Rural do Semi-Árido, 2019)
Family farming in the Brazilian Northeast is characterized by simplicity, low levels of technology and little access to water, mainly of quality, insufficient for large-scale production when one considers the low purchasing power of family producers. With long periods of drought and few financial resources, family farmers have brought their produce closer to home in their backyards, enabling them to offer safe food for themselves and their families, as well as the possibility of selling excess production. Thus, government programs such as the Food Acquisition Program (PAA) and National School Feeding Programs (PNAE), which help in the purchase of these products, through associations, guaranteeing the sale and continuity of production. The present qualitative and quantitative research was carried out through the application of questionnaires to family farmers from two regions of Apodi / RN, explaining the production in productive yards and the influence of government purchases in their production in 2017, and also through their own experience in work performed within the cooperatives and knowledge of the procedures. Bibliographical sources were also used to discuss the theme and data collected, allowing a better understanding of the problem. In the results obtained through questionnaires about the importance of sales of its products for these government procurement programs, most were satisfied with sales, offering a diversity of products and thus allowing them to stay in the field. Through the purchase incentive, the family farmers remain in rural areas producing in an agro-ecological way, without the need to go to the city in search of other forms of employment, but they can still be consortium of the same, and also making possible the supply of employment for their families, removing the need to leave their culture and routine of origin. The PAA and PNAE programs are therefore of great importance for the continuity of productive farms in Apodi, because it is through them that farmers feel encouraged to produce more and have the proper sale of their products in a fair and accessible way.
Monografia
Keywords: Agroecologia; Semiárido; Agricultura familiar; Agroecology; Semiarid; Family farming; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO::EDUCACAO RURAL